Pre-marital Sexual Behavior of Adolescents: The Influence of Self-Control, Parental Attachment, and Peer Roles: Pre-marital Sexual Behavior of Adolescents: The Influence of Self-Control, Parental Attachment, and Peer Roles - Zahro Malihah; Melly Latifah; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Pre-marital sexual behavior in adolescents is influenced by personal, family, and environmental factors, including peer groups. This study aims to analyze the influence of adolescent-parental attachment, self-control, and the role of peers on the pre-marital sexual behavior of high school/vocational high school adolescents. This explanatory research was conducted purposively at SMA and SMK in Bogor city. Data collection was carried out voluntarily using a questionnaire via google form in January 2022. Respondents in this study were 245 teenagers who had unmarried criteria and still had intact parents. The results showed that the majority of adolescent pre-marital sexual behavior was in the